Legal regulation of the distribution of general seats in parliamentary elections - Ismail Najmaddin Zangana; Zana Jalal Saeed (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
Human thought is continuously in search of the best electoral systems, mechanisms, and their application to embody the opinion of voters in the outcome that result from the elections, We observe that majority of the studies related to elections include the examination of electoral systems according to different criteria, and if any form of election is adopted, it is then divided into direct elections and indirect elections, if the method of candidacy is adopted then the election shall either be single-member plurality voting system or proportional representation. In the case of the criterion concerning the mechanism of counting votes, the election shall have three forms: majoritarian election, proportional representation and mixed elections. Most of these electoral systems have been adopted by states at different stages taking into consideration the political and social environment of these states; in particular, the systems that is concerned with how votes are calculated and the distribution of parliamentary seats, whether by majority or proportional representation, or mixed system. Each of the three electoral systems specifically depends on different processes, mechanisms and equations for filling the parliamentary seats. In accordance to and under the constitutional framework, the legislator’s vision of the state at a certain stage in the history of the state, and whether the legislator has supported the bipartisan system (A two-party system) or downsize the number of political parties participating, then the majority system becomes the most appropriate choice. And, if consideration is given to a multiparty and pluralistic representation to be adopted in parliament, the system of proportional representation is the best option. In case of the legislator desiring to collect the positive points of the majority system and the system of proportional representation, the mixed system is the most successful and secure. and these systems are the focus of our research, which will be discussed in the context of two sections, the First Section: was devoted to examining the three electoral systems extensively, and the Second Section: the equations adopted in the distribution of parliamentary seats on the individuals or winning lists with deliberations given to the mechanisms applied in Iraq and the Kurdistan Region. And the study has reached a set of results and proposals.